2013
DOI: 10.5395/rde.2013.38.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of operator's experience level on lifespan of the WaveOne Primary file in extracted teeth

Abstract: ObjectivesThe aim of this study was to assess the influence of operator experience level on the lifespan of the WaveOne Primary file (Dentsply Maillefer, Ballaigues, Switzerland) in extracted teeth.Materials and MethodsModerately curved canals of extracted maxillary and mandibular molars were randomly distributed into 2 groups: experienced and inexperienced operators. Ten files were allocated to each group (n = 10). Each canal was prepared until the working length was reached, and the same file was used to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…However, this does not invalidate laboratory investigations that provide hypotheses for clinical studies or for ex vivo studies conducted on extracted teeth (Saleh et al . 2013, Pirani et al . 2014, Cassimiro et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not invalidate laboratory investigations that provide hypotheses for clinical studies or for ex vivo studies conducted on extracted teeth (Saleh et al . 2013, Pirani et al . 2014, Cassimiro et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In addition, the systems have different amplitudes of cutting movement, being 150° for Reciproc and 170° for WaveOne. Although recent studies have demonstrated that there is no difference in the percentage increase in area after instrumentation with the R25 and Primary files,[ 21 22 ] when one associates the wider angle of advance in the cutting direction (counter-clockwise) of the WaveOne system with the lower depths of its grooves, this may explain the inferior performance in regard to debris removal during instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…15,48 Further reports show that file deformation and life span are not influenced by operator experience or the establishment of a mechanical glide path. [49][50][51] Wan et al claim that reciprocating files undergo decreased stress and should therefore have a greater fatigue resistance because these files travel shorter circumferential distances than do rotary files. 52 Various studies have concluded that the reciprocating motion extends the life span of NiTi endodontic files.…”
Section: A Smooth Transition Between Instruments Because Of a Design mentioning
confidence: 99%